2016 XLII Latin American Computing Conference (CLEI) 2016
DOI: 10.1109/clei.2016.7833356
|View full text |Cite
|
Sign up to set email alerts
|

Exploring differences in how learners navigate in MOOCs based on self-regulated learning and learning styles: A process mining approach

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
1
10
0
10
Order By: Relevance
“…In our program, a significant percentage showed interest in attending but never participated, while an equally significant percentage left the program during the first weeks, confirming a number of other studies (Dillahunt, Wang, & Teasley, 2014;Gütl et al, 2014;Heutte, Kaplan, Fenouillet, Caron, & Rosselle, 2014;Ho et al, 2014;Perna et al, 2014;Santos, Klerkx, Duval, Gago, & Rodríguez, 2014;Stein & Allione, 2014;Tucker, Dickens, & Divinsky, 2014;Whitmer et al, 2014;Wilkowski, Deutsch, Russell, 2014;Greene, Oswald, & Pomerantz, 2015;Kleiman, Wolf, & Frye, 2015;Koedinger, Kim, Jia, McLaughlin, & Bier, 2015;Lackner, Ebner, & Khalil, 2015;Skrypnyk et al, 2015;Allione & Stein, 2016;Davis, Chen, Jivet et al, 2016a;Evans, Baker, & Dee, 2016;Fidal-go-Blanco, Sein-Echaluce, & García-Peñalvo, 2016;Maldonado et al, 2016;Tseng, Tsao, Yu, Chan, & Lai, 2016;Crosslin, Dellinger, Joksimovic, Kovanovic, & Gaševic, 2017;Tawfik et al, 2017).…”
Section: Research Questionsupporting
confidence: 63%
“…In our program, a significant percentage showed interest in attending but never participated, while an equally significant percentage left the program during the first weeks, confirming a number of other studies (Dillahunt, Wang, & Teasley, 2014;Gütl et al, 2014;Heutte, Kaplan, Fenouillet, Caron, & Rosselle, 2014;Ho et al, 2014;Perna et al, 2014;Santos, Klerkx, Duval, Gago, & Rodríguez, 2014;Stein & Allione, 2014;Tucker, Dickens, & Divinsky, 2014;Whitmer et al, 2014;Wilkowski, Deutsch, Russell, 2014;Greene, Oswald, & Pomerantz, 2015;Kleiman, Wolf, & Frye, 2015;Koedinger, Kim, Jia, McLaughlin, & Bier, 2015;Lackner, Ebner, & Khalil, 2015;Skrypnyk et al, 2015;Allione & Stein, 2016;Davis, Chen, Jivet et al, 2016a;Evans, Baker, & Dee, 2016;Fidal-go-Blanco, Sein-Echaluce, & García-Peñalvo, 2016;Maldonado et al, 2016;Tseng, Tsao, Yu, Chan, & Lai, 2016;Crosslin, Dellinger, Joksimovic, Kovanovic, & Gaševic, 2017;Tawfik et al, 2017).…”
Section: Research Questionsupporting
confidence: 63%
“…In the set of selected papers there is a tendency of using Zimmerman's (Hood et al, 2015;Min & Jingyan, 2017;Littlejohn et al, 2016) or Pintrich's (Kizilcec et al, 2016;Alario-Hoyos et al, 2017;Kizilcec et al, 2017) self-regulation models, or a mix of both (Jansen et al, 2017;Maldonado et al, 2016), which is consistent with the findings of Panadero (2017). However, the base of most selected studies is unknown because they do not specify the chosen SRL model or consider several sub-processes which are not specific to one model.…”
Section: Rq4: What Are the Topics Of Analysis And Aspects Of Srl Takementioning
confidence: 99%
“…Task strategies refer to learners' ability to identify and use learning approaches or strategies to learn effectively, as well as adapting them throughout the performance phase. Among the selected documents, a variety of task strategies were identified such as note-taking , completing several consecutive lectures (Maldonado et al, 2016) or delving into the topic through external material (Littlejohn et al, 2016). Furthermore, low and high self-regulators differ in their approach towards learning and the adaptability of their strategies (Littlejohn et al, 2016).…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The main focus of the literature review reported in this document is the work that has been developed in supporting self-regulated learning as a process that must be endorsed in the context of MOOCs, so that participants can conclude satisfactorily their learning progress in these massive online courses [20], [21].…”
Section: Introductionmentioning
confidence: 99%